Gondari voices: legends from Nothern Ethiopia - Ramos, M.; manuel.ramos@iscte-iul.pt (Gondari Voices – Legends from Northern Ethiopia is a short film shot and edited by Manuel João Ramos (researcher at CEI-IUL), based on popular oral stories about a turbulent period in Ethiopian political and religious history. The narrators, local elders who perpetuate ancient Amhara oral traditions, weave a series of interconnected tales about a sacred quest of the Ethiopian kings for a site to f, 2018)
Gondari Voices – Legends from Northern Ethiopia is a short film shot and edited by Manuel João Ramos (researcher at CEI-IUL), based on popular oral stories about a turbulent period in Ethiopian political and religious history. The narrators, local elders who perpetuate ancient Amhara oral traditions, weave a series of interconnected tales about a sacred quest of the Ethiopian kings for a site to found the kingdom’s capital, and their fantastical interactions with angels, foreigners, prophets and holy slaves. The film is a complement to the book by the same author: Of Hairy Kings and Saintly Slaves – An Ethiopian Travelogue (Oxford, Kingston Publishing, Aug. 2018).